The Effect Of Leadership Style, Human Resources Quality and Organizational Citizenship Behavior (OCB) on Organizational Commitment In Communication Mediation at BPJS Ketenagakerjaan Nias Gunungsitoli & North Medan - Dedita Vicky Tarigan; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to analyze the effect of leadership style, human resource quality, and organizational citizenship behavior (OCB) on organizational commitment with communication as a mediating variable at BPJS Employment Nias Gunung Sitoli and Medan Utara. This research employs a quantitative approach using a survey method. The research sample consists of 100 employees selected through a saturated sampling technique. Data were collected using questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that leadership style and communication have a positive and significant effect on organizational commitment. Human resource quality and OCB do not have a direct effect on organizational commitment. However, human resource quality and OCB have a positive and significant effect on communication. Furthermore, communication is proven to mediate the effect of human resource quality on organizational commitment, but it does not mediate the effect of leadership style and OCB on organizational commitment. The findings of this study are expected to provide managerial implications for improving organizational commitment through strengthening leadership style, human resource quality, and effective communication.